Tantalum ion acceleration in laser‐generated plasma and dependence on the pulse duration. Issue 9 (28th June 2019) - Torrisi, L.; Cutroneo, M.; Torrisi, A.
Abstract : The laser irradiation of tantalum targets is presented for different pulsed laser intensities ranging from 10 10 up to about 10 18  W/cm 2 and pulse durations from 9 ns up to 40 fs. The results show that the produced non‐equilibrium plasma accelerates Ta ions in the backward direction from values of the order of keV up to values of about 5 MeV. In thin foils, the forward plasma, developed behind the target along the direction of incoming laser, at intensities of about 10 16  W/cm 2 and 300 ps pulse duration, accelerates Ta ions at energies of the order of 4.6 MeV and produces charge states up to about 40+. For fs lasers at intensities of the order of 10 18  W/cm 2, only proton acceleration occurs up to 2.1 MeV while no Ta ions are accelerated, due to the reduced duration of the electric field and to the too high inertial mass of the Ta ions.